La falta de educación financiera y su incidencia en el sobre endeudamiento de la sociedad en la ciudad de Riobamba en el año 2024. - Olivo Olivo, Junior Alexander (2025)
The central theme of this research is the lack of financial education and its impact on over- indebtedness in society in the city of Riobamba in 2024, with the general objective of analyzing the level of financial literacy among the individuals under study. To this end, a quantitative, qualitative, and mixed-methods approach was employed, as the study was non-experimental, to determine the percentage of people who possess knowledge about managing monetary resources (money). One of the tools used to collect information was a survey, which proved fruitful in identifying the main cause of the lack of financial knowledge. Once the survey was conducted, it was determined that many people do not keep track of their income and expenses because they did not receive an education that instilled in them the habit of managing their money efficiently. This led us to the conclusion that it is necessary to provide training and guidance to society at large on the proper use and management of money.